(untitled) (Mustansiria Dental Journal, 2018)
In this study, the relationships between the over bite and the structure of the frontal alveolar and basal bone were investigated. The over bite, lower face height, and the anterior alveolar and basal midsagittal cross-sectional area from the maxilla and the mandible were assessed on lateral cephalograms from (88) un-treated subjects. The open bite group showed significantly larger maxillary and mandibular alveolar and basal cross sectional areas compared with the normal over bite group. It is concluded that open bite subject with long face have a larger mandibular and maxillary alveolar height, which is more associated with elongated and narrowed shape of the symphysis